ARROWHEADS WITH “SIDE SPIKES” IN THE MILITARY EQUIPMENT OF THE NORTH-CAUCASIAN POPULATION IN THE SECOND HALF OF THE II – EARLY I MIL. BC - Burkov, Sergej Borisovic (History, Archeology and Ethnography of the Caucasus, 2022)
The article explores the issue of emergence and development of the practice of using bone and bronze arrowheads with the so-called “side spikes” by the population of the Central and North-Eastern Caucasus. For this purpose, materials from common and burial sites of the region were involved. We discovered that the arrowheads with blades (“stingers”) pointed down first appeared in the territory of Transcaucasia in the second half of the II millennium BC. Collected materials suggest that the arrowheads with one or two additional side “spikes” in that time period were recorded only on the territory of the North Caucasus. Originally, they were made from bone. Such finds were recorded on the territory of Dagestan. Subsequently, this type of armament was also found in single samples of bronze in the form of flat arrowheads, taking it origins from the territory of Transcaucasia. This kind of heads did not become popular among the peoples who lived in the Central and North-Eastern Caucasus. Later, the side spike became widespread only at the early stage of the “Scythian” period, first on two-blade heads, and then on three- and four-blade tips. However, the very idea of this type of weaponry first appeared among the Caucasian tribes back in the developed Bronze Age, and their use survived until the beginning of the first third of the 1st millennium BC.
Keywords: North Caucasus; arrowheads; side spike; Late Bronze Age; Early Iron Age